Communication as a right or public service from the communication law of Ecuador - Suing Ruiz, A. (2016)
© 2016 AISTI.The Organic Law of Communication of Ecuador defines social communication as a public service, this concept generates positions contrary to its definition and the relationship with the rights of citizens. The objectives of the research are to analyze the impact of the concept in the Ecuadorian news media; determine the arguments of the communication as a public service; and evaluate the decisions of the supervisory authority. The methodology is qualitative and quantitative through interviews, content analysis and revision of the statistics of the Superintendency of Communication. The study concludes that the definition of communication as a public service shows no contradiction with some legal traditions or affects the freedom of expression; it also reflects imbalance in the information of the print media; and; that the decisions of the Superintendent serve the compliance of rights rather than the relationship of public services.